Plan de mejoramiento empresarial de la cadena de restaurantes Troncos Parrilla en la ciudad de Pereira (2012)
Troncos parrilla is a restaurant chain that is currently giving a service to the public, elaborating products ready for the consumption in the city of Pereira The development of the following research work has as a primary objective the improvement of the quality of service provided by the enterprise troncos parrilla The work in reference it is based on the application of the continuous improvement as a management technique to achieve the quality and on administrative tools that contribute to the solution of organizational problems and in the achievement of the following objectives  Satisfy the costumer 100%  Achieve a positioning and recognition of the brand  Contribute socially and economically to the country by generating jobs  Excellence in quality of products  Hire staff that has a profile of responsibility, dedication, integrity, leadership, professionalism and above all great customer service The growth of the enterprise will be achieved by a strategic addressing, which includes change of corporate image, fulfillment of the standards of production and quality, adjusting the quality of the products to the requirements of the customers, publicity, constant training of the staff, accomplishing a remembrance of the brand and identity of the flavors The enterprise will show a better image to its customers and it will efficiently do its internal management, restructuring the main activities that produce a revenue for the company and likewise direct it to find its product-market balance leading it to a growth and projection to the future.